The Impact of Work Motivation and Compensation on Job Satisfaction among Tourism Employees in Manado City - Helni Desty Yanice Lagarense; Agus Soegoto; Joubert Maramis; Hendra Tawas (Jurnal Internasional Riset Bisnis Pariwisata, 2026)
This study examines the effects of work motivation and compensation on employee job satisfaction in the tourism sector in Manado City, Indonesia. While previous tourism human resource management studies have extensively investigated job satisfaction in hospitality settings, limited research has explored how motivation and compensation influence employee satisfaction amid ongoing changes in the tourism industry. This study addresses this gap by investigating employee job satisfaction in contemporary hospitality workplaces characterized by evolving organizational and service demands. A quantitative approach with a cross-sectional survey design was employed. Data were collected from 77 employees of Hotel Luwansa Manado and Roger's Hotel Manado using purposive sampling. The research instrument consisted of validated questionnaire items measured on a five-point Likert scale. Data were analyzed using multiple linear regression with IBM SPSS Statistics version 26. The findings indicate that work motivation has a positive and significant effect on job satisfaction (B = 0.412; t = 4.983; p < 0.001), making it the strongest predictor in the model. Compensation also has a positive and significant effect on job satisfaction (B = 0.389; t = 4.701; p < 0.001). Simultaneously, both variables explain 55.8% of the variance in employee job satisfaction (R² = 0.558; F = 47.231; p < 0.001). This study contributes to tourism workforce literature by demonstrating that motivation remains a stronger determinant of job satisfaction than compensation in contemporary hospitality settings. The findings highlight the importance of balancing intrinsic motivational practices with fair compensation systems to improve employee satisfaction and retention. Practical implications suggest that tourism businesses should strengthen employee development, recognition programs, and compensation policies to enhance workforce sustainability and organizational performance.